ANALISIS PENGARUH CASH FLOW TERHADAP KEBIJAKAN DIVIDEN PERUSAHAAN DENGAN SIZE PERUSAHAAN DAN LIFE CYCLE PERUSAHAAN SEBAGAI MODERATING VARIABLE - Leditya Jayati; Nur Cahyonowati (Diponegoro Journal of Accounting, 2014)
Dividend income is taken from internal-financing which is the revenue. Inconsistencies results of previous studies primarily on the cash flow factor is the basis for this research by developing an analytical model of BCG as a moderating variable logic basic. This study aimed to examine the effect of cash flow relationship (CFPS) on the payment of dividends (DPS) with size (SIZE) and life cycle (LC) company as a moderating variable , as well as profitability (EPS) and leverage (DR) as a control variable.The sample are manufaturing company listed on the Indonesia Stock Exchange for years 2010-2012 totaling 133 companies, and the sample is toke with purposive sampling method. The analysis technique used here is a linear regression.The results of this study, based on t-test showed that (1) significant positive effect of cash flow on the payment of dividends, (2) a significant positive effect of firm size on the relationship between cash flow to the payment of dividends, (3) significant positive effect of life cycle on the relationship between cash flow to dividend payment. The test results of coefficient of determination (R2) in this study showed the number 0.798 for the model (1), 0.816 for the model (2), and 0,812 for the model (3). This means that 79,8% of DPS is affected by CFPs, EPS, and DR for the model (1), while the rest is explained by other variables. So does with the model (2) as much as 81,6 % of DPS is affected by the CFPS and moderating SIZE & controls, and 81,2 % DPS influenced by CFPS and moderating LC & controls, while the rest is explained by other variables .